Port of Spain Summit Declaration as a successful outcome of globalhealth diplomacy in the Caribbean region: a systematic review - Vijay Kumar Chattu; Andy W Knight (Tabriz University of Medical Sciences, 2019)
Background: The Caribbean region, with a population of around 17 million, has the highest burden of chronic noncommunicable diseases (NCDs) in the region of the Americas. It is estimated that diabetes and hypertension has an economic impact of around 5%-8% of the gross domestic product of the region. The purpose of this study was to explore and understand how global health diplomacy contributed to the evolution of a collective Caribbean regional summit declaration to address the epidemic of NCDs. Methods: A systematic review was conducted, and all the major databases such as MEDLINE, PubMed, EMBASE, Scopus, Web of Science, EBSCO, Global Health database and other available policy documents from various sources were screened. All articles available from 1910-2018were extracted. From the total of 3223 titles, after filtering, the search narrowed down to 28full texts that are included in this study. Policy documents and articles related to NCDs, global health diplomacy, and the Port of Spain Declaration (POSD) were the focused themes. Results: The Caribbean region showed significant commitment to the prevention and control of NCDs through its united voice and commitment since 2001. The successful rounds of negotiations for regional health have led to the formulation of the 15- point multisectoralPOSD "Uniting to Stop the Epidemic of Chronic NCDs." This was the first Summit in the world where the Heads of Government focused on prevention and control of NCDs with a clear road map for policy implementation, collaboration, and collective action. This regional summit declaration gained global attention and resulted in the United Nations Political Declaration on the Prevention and Control of NCDs and as WHO Global Action Plan for the Prevention and control of NCDs 2013-2020. Conclusion: There is enormous scope for this evolving area of Global Health Diplomacy in addressing the future challenges of health security.